IIHR, Bengaluru, serving for nutritional and livelihood security - Dutt, Som (Indian Horticulture, 2019)
Oftenly nicknamed as the ‘mother of all horticultural institutes’ in India, the IIHR, Bengaluru, has contributed tremendously towards research and developmental activities of all horticultural crops. The institute has developed many entrepreneurs and progressive farmers and has boosted our industries in the field of canning, freezing and by other value-added products through its technological intervention. A number of varieties and hybrids developed by institute have revolutionized the production of horticultural crops in the country. Thus IIHR, Bengaluru, has played a catalytic role in the field of all round horticultural development. Now, the institute under the leadership of dynamic and visionary horticulturist, Dr MR Dinesh, promises to go a long way in meeting all the emerging challenges.